INCOME STRUCTURE ANALYSIS OF VANNAMEI (Litopenaeus vannamei)SHRIMP FARMING IN SUB-DISTRICT OF SECANGGANG, DISTRICT OF LANGKAT - Sri Ulina; Satia Negara Lubis; Matius Bangun (JURNAL PROINTEGRITA, 2019)
The aim of the research is to analyse the income structures of shrimp Vannamei farmers in the research area, analyzing the feasibility of farming on the income structures of shrimp vannamei in the research area, analyzing the influence of Benur, Feed, vitamins, fertilizer, medicines, FUEL, TKLK and prices on the income of shrimp Vannamei fertiliser in the research area and to educate the relationship of Benur, feed, vitamins, medicines, fertilizer, FUEL, TKLK, and price to the income structure Shrimp Vannamei in the research area. This research was conducted in Secanggang district of Langkat District. The determination of the research area is done purposive sampling which is to take the sample done intentionally, with the sample record representative or represent the population. The study was conducted from February to May 2019. The number of samples used in this study was 30 respondents. Data analysis is done in a descriptive and multiple linear regression analysis. Average income cultivating Shrimp Vannamei in District Secanggang Langkat of the main income of shrimp farming vannamei of Rp. 67.641.036,667 and from the side business is the fisheries Business (Nila) of Rp. 8.506.700, Business Agriculture (paddy Rice) amounting to Rp. 4.116.775 and non agriculture amounting to Rp. 7.300.000, with 77.25% revenue structure and 22.75% revenue share. Farming in Secanggang district of Langkat District is feasible to be cultivated with a comparison of R/C > 1. In unison of the F test results; Benur, feed, vitamins, medicines, fertilizer, FUEL, TKLK, and price, significant influence on income. Partially from the test results t that; Variable Benur, feed, FUEL and price significantly affect the income of shrimp vannamei, while vitamins, medicines, fertilizers and TKLK have no significant effect on the income of shrimp Vannamei fertiliser. Relation of Benur, feed, vitamins, medicines, fertilizer, FUEL, TKLK, and the price of the income structure of shrimp Vannamei in the District Secanggang District Langkat is that the Benur, feed, FUEL, and prices relate significantly to Revenue structure of shrimp vannamei, which means the amount of cost incurred will affect the magnitude of income structure of shrimp Vannamei. Meanwhile, vitamins, medicines, fertilizer, and TKLK related to insensitivity to the income structure of shrimp vannamei, which means that the low cost incurred will affect the magnitude of the income structure of shrimp Vannamei Received.